Peran Institusi Lokal Dalam Pembentukan Habitus Siaga Dan Pengembangan Mitigasi Bencana Di Kawasan Gunung Kelud Kabupaten Kediri - Windiani Windiani; I.B. Wirawan; Sutinah Sutinah (Institut Teknologi Sepuluh Nopember, 2019)
This study aims to explore the role of local institutions in the establishment of preparedness habitus and the development of disaster mitigation in Mount Kelud area of Kediri Regency using the structural-constructivist approach of Pierre Bourdieu. This research is qualitative research in nature so that the data collection is conducted by participant observation, document tracking, and in-depth interview. The results showed that local institutions that play a role in the formation of disaster prepared habitus and mitigation development in the Mount Kelud area are formal institutions e.g. BPBD of Kediri, District and Village, and informal institutions namely the Jangkar Kelud Community and the Village Disaster Preparedness Team. The research also found that collaborative roles between leaders and local leaders have contributed greatly to the formation of disaster preparedness habitus for residents of Mount Kelud Slopes. This evident showed when residents of Mount Kelud were able to evacuate and rescue independently and could minimize casualties and adapt to the current situation when Mount Kelud erupted in 2014. In the formation of preparedness habitus and disaster mitigation leaders and local leaders use the knowledge and local wisdom as capital value to develop the attitude of life